The Nature and Limits of Human Equality - Charvet, John. author. aut Link
X, 188 p.
Keywords: The belief in equality as the basis of a just society is fundamental to the dominant western, liberal viewpoint. Yet, the standard individualist justification for it is weak and contradictory. This book provides a radically new communitarian account of the value of equality and establishes it's proper limits.